The determinants of efficiency of publicly listed Chinese banks: evidence from two-stage banking models - Sufian, Fadzlan (Taylor & Francis, 2009)
The paper attempts to investigate the long-term trend in the efficiency of the Chinese banking sector over the period 1997–2006 by employing the Data Envelopment Analysis (DEA) window analysis method. We find that the small banks have exhibited the lowest mean technical efficiency compared to their medium and large bank peers, while the medium-sized banks were relatively more technically efficient compared to their small and large bank counterparts. The empirical findings suggest that the Joint Stock Commercial Banks (JSCBs) have been relatively more technically efficient compared to their State-Owned Commercial Bank (SOCB) counterparts attributed to higher mean scale efficiency. On the other hand, the SOCBs have outperformed their JSCB counterparts in terms of pure technical efficiency. The results from the second-stage regression analysis suggest that technical efficiency is positively associated with diversification, loans intensity, capitalization levels, and economic growth. On the other hand, technical efficiency is negatively related to size and expense preference behaviour.